Contribuição para a silvicultura de Luehea divaricata Martius et Zuccarini (Açoita-cavalo) - Farias, Jorge Antonio de (2006)
The goal of this paper is to evaluate the growth of the seedlings, in different sizes and recipients, with different types of substracts. The experiment was established and conducted on the premises of the Forestry Science Silviculture Laboratory of the Federal University in Santa Maria, located in the Central Depression Area of the State, in the municipality of Santa Maria, State of Rio Grande do Sul, and the area is at an approximate altitude of 90 to 95 meters, its geographic location is between parallels 20º43 and 29º44 latitude south, and between meridians 53º42 and 53º44 longitude west of Greenwich. Statistical delineation utilized was an entirely casualized block, and as the treatment consisted of different recipientss and different substracts, the bifactoral system was adopted, with 16 treatments and 4 repetitions. On average, 96 plants were seeded in each parcel, and with the exclusion of the two border rows, 32 useful plants were obtained. The seeds came from Afubra s Socioenvironmental Program, a sub-project of the Native Tree Seed Pouch program. Three seeds were sown into each recipient and later submitted to thinning out. Evaluations started 90 days after seeding, and were concluded in 180 days, taking into consideration stem diameter, size of seedlings, dry root weight, dry aerial weight, and the Dickson quality rate. Using the variance analysis and average comparison test, through the Tukey test, there were no significant differences in the analyzed parameters for the following variables: stem diameter; size of seedlings; dry root weight, dry aerial weight and Dickson quality rate, among the 180 cm³ and 280 cm³ cells. For the variables: stem diameter, dry root weight, and Dickson quality rate, the best media was the so-called Plantmax Agrícola. For the seedling size and dry aerial weight variables, the best media was defined as Humosolo Vida. Based on these results, it is possible to recommend 180-cm³ recipients, for their economic advantages in terms of less material, less labor and smaller transport costs. The recommended media is the Plantmax Agrícola, which has so far produced the best results in terms of seedling quality patterns.